2022
DOI: 10.1039/d2ta06216j
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably enhanced Fenton-like catalytic activity and recyclability of Fe-based metallic glass by alternating magnetic field: mechanisms and industrial applications

Abstract: Fenton-like processes by heterogeneous catalysts present a promising strategy for ever-growing water pollution problems. However, developing low-cost catalysts with sustainability in both high catalytic efficiency and good recyclability remains challenging....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Metallic glasses (MGs) exhibit an exclusive combination of characteristics, i.e., when compared to crystalline counterparts, nanostructured MGs have higher potential for passivation along with lower passivation current, high catalytic efficiency, outstanding mechanical strength and elastic limit, as well as remarkable wear and fatigue resistance. [1][2][3][4][5][6][7][8][9][10] Compared to crystalline metallic alloys, the non-translational atomic clusters constituting MGs on the nanometer scale and the free volume in between enable a higher number of hydrogen interactions. 11,12 Hence, these materials have been suggested as green energy materials for hydrogen storage and production.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic glasses (MGs) exhibit an exclusive combination of characteristics, i.e., when compared to crystalline counterparts, nanostructured MGs have higher potential for passivation along with lower passivation current, high catalytic efficiency, outstanding mechanical strength and elastic limit, as well as remarkable wear and fatigue resistance. [1][2][3][4][5][6][7][8][9][10] Compared to crystalline metallic alloys, the non-translational atomic clusters constituting MGs on the nanometer scale and the free volume in between enable a higher number of hydrogen interactions. 11,12 Hence, these materials have been suggested as green energy materials for hydrogen storage and production.…”
Section: Introductionmentioning
confidence: 99%
“…However, there remains some shortcomings for ZVI in industrial organic wastewater treatment, among which the insufficient activity of iron is the most concerned issue. Various attempts have been made to settle the problem in previous works [6][7][8][9]. An effective way to improve the degradation performance is to increase the specific surface area [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, introducing an external field (e.g., thermal, electric, magnetic, and mechanical) would lead to improved efficiency of an existing catalytic system. [1][2][3][4][5][6] Among reported routes, the employment of a magnetic field has been considered as an effective strategy, and significant advances have been achieved in different catalysis fields, including photocatalysis, [7][8][9][10][11] electrocatalysis, [11][12][13][14][15][16][17] and thermocatalysis, [18] leading to significantly enhanced performance and allowing for wireless control of catalytic reactions. [19,20] It is concluded that magnetic fields can affect the spin polarization of magnetic materials, thereby accelerating the movement of free charge carriers and increasing the rate of electron transfer to the surface and generation of free radicals participating in catalytic reactions.…”
mentioning
confidence: 99%